Mental Representations of the Text Surface, the Text Base, and the Situation Model in Auditory and Audiovisual Texts in 7-, 9-, and 11-Year-Olds. Issue 3 (3rd April 2018) - Wannagat, Wienke; Waizenegger, Gesine; Hauf, Juliane; Nieding, Gerhild
Abstract : This study investigated the effects of auditory and audiovisual text presentation on the three levels of mental representations assumed in theories of discourse processing. A sample of 106 children aged 7, 9, and 11 years listened to 16 short narrative texts, 8 of which were accompanied by a series of pictures illustrating the content. Participants' memory of text surface, text base, and situation model was then assessed, using a sentence recognition test. The results indicate that mode of presentation affects memory at every level and in every age group. Memory of text surface and situation model was better at audiovisual presentation, whereas memory of the text base was better at auditory presentation.